Biochemistry, Synthesis, and Applications of Bacterial Cellulose: A Review - Mishra, Snehasish; Singh, Puneet Kumar; Pattnaik, Ritesh; Kumar, Subrat; Ojha, Sanjay Kumar; Srichandan, Haragobinda; Parhi, Pankaj Kumar; Jyothi, Rajesh Kumar; Sarangi, Prakash Kumar (Frontiers in Bioengineering and Biotechnology, 2022)
The potential of cellulose nanocomposites in the new-generation super-performing nanomaterials is huge, primarily in medical and environment and secondarily in food, paper, and cosmetics sectors. In spite of substantial illumination on the molecular aspects of cellulose synthesis, various process features viz., cellular export of the nascent polysaccharide chain, arrangement of cellulose fibrils into a quasi-crystalline configuration, etc. remain obscure. To unleash its full potential, current knowledge on nano-cellulose dispersion and disintegration of the fibrillar network and the organic/polymer chemistry need expansion. Bacterial cellulose biosynthesis mechanism for scaled-up production, viz., the kinetics, pathogenicity, production cost and product quality/consistency remain poorly understood. The bottom-up bacterial cellulose synthesis approach makes it an interesting area for still wider and promising high-end applications, primarily due to the nano synthesis mechanism involved and the purity of the cellulose. The paper attempts to identify the knowledge gap, potential wider applications of bacterial cellulose and bacterial nano-cellulose. This review also highlights the manufacture of bacterial cellulose through low-cost substrates i.e., mainly waste from brewing, agriculture, food and sugar industries as well as textile, lignocellulosic biorefineries and pulp mills.